Dietary patterns and their impact on public health: A case study of Multan, Pakistan - Fatima, Sonia; Zubair, Asim; Ying, Haihua (Abdul Media Literasi, 2025)
The health field concept states that lifestyle is the most significant element influencing health. The complex process of ageing is influenced by a variety of factors that determine whether a person may develop age-related chronic diseases in their later years. These variables encompass various behavioural, environmental, and dietary factors. A healthy diet is crucial for maintaining overall well-being. One of the primary objectives of this research was to assess people’s understanding of dietary patterns. “Nutritional pattern and its impacts upon the health of citizens” was the focus of the current quantitative investigation. The current study was conducted in the city of Multan, Pakistan. The study also examines the connection between fast food and its effects on citizens’ health. The sample size consisted of 200 respondents, who were selected using basic random sampling techniques. A questionnaire was employed as a data collection instrument. As a result, statistical methods were used to gather, analyse, and interpret the data. The purpose of the current study was to investigate attitudes, practices, and knowledge related to dietary patterns. The main conclusion is that while fast food has adverse health effects, most respondents believe that healthy eating is a key factor in achieving longevity. Some respondents said that overeating was the cause of their illnesses. Many people believe that a balanced diet is an easy way to maintain good health, while it also plays a vital role in the better health of pregnant and lactating women. The study recommended that consumers avoid fast food and overeating and instead follow a balanced diet.